The effectiveness of teamwork on work performance among McDonald’s employee in Kota Bharu. - Mohd Firdaus Amran (2019)
Generally, this project aims to study the factors which could affect the effectiveness of teamwork on work performance among McDonald’s employee in Kota Bharu. This study was carried at McDonald’s Kota Bharu and the respondents are among the McDonald’s workers. Four factors have been found to be related to the study and the factors are trust, communication, leadership, and personality. All the four factors are independent variables for the study. Questionnaire have been used to obtain related feedback from the respondents and collecting data whereas to analyse the data, Pearson Correlations Analysis and Independent sample test are used. The result found after analysing the data are for items from hypothesis was significant.